Learn Math Questions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Solve x^{2} + 4x − 12. x = 2, x = 6, x = −2, x = −6, x = 3, x = −4, x = −3, x = 4

The above quadratic equation is in the form of ax^{2 }+ bx + c.

## Answer: For the equation x^{2} + 4x − 12, x = 2, -6

Substituting the values of x in the given quadratic equation.

**Explanation:**

f(x) = x^{2} + 4x − 12

If x = 2, (2)^{2} + 4(2) - 12 = 4 + 8 - 12 = 0

If x = 6, (6)^{2} + 4(6) - 12 = 36 + 24 - 12 = 48

If x = -2, (-2)^{2} + 4(-2) - 12 = 4 - 8 - 12 = -16

If x = -6, (-6)^{2} + 4(-6) - 12 = 36 - 24 - 12 = 0

If x = 3, (3)^{2} + 4(3) - 12 = 9 + 12 - 12 = 9

If x = -4, (-4)^{2} + 4(-4) - 12 = 16 - 16 - 12 = -12

If x = -3, (-3)^{2} + 4(-3) - 12 = 9 - 12 - 12 = -15

If x = 4, (4)^{2} + 4(4) - 12 = 16 + 16 - 12 = 20

### Therefore, after solving the x values, we get the solution as x = 2, -6

Math worksheets and

visual curriculum

visual curriculum